2012
DOI: 10.4238/2012.august.13.6
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis demonstrates that the NAD(P)H: quinone oxidoreductase 1 (NQO1) gene 609 C>T polymorphism is associated with increased gastric cancer risk in Asians

Abstract: ABSTRACT. The association between the NAD(P)H: quinone oxidoreductase 1 (NQO1) gene C609T polymorphism and gastric cancer has been widely evaluated, yet with conflicting results. Data were available from seven study populations involving 2600 subjects. Overall, comparison of alleles 609T and 609C indicated a significantly increased risk (46%) for gastric cancer (95% confidence interval (95%CI) for odds ratio (OR) = 1.20-1.79) in individuals with the T allele. The tendency was increased in the homozygous compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Patients with the 609TT and the 609CC genotypes were compared and a strong correlation was observed (OR = 2.04, 95% CI = 1.37-3.05). These authors concluded that the 609C > T polymorphism of the NQO1 gene increases the risk for developing stomach cancer, especially in the Asian population [23]. Similar results were obtained by Liu et al [24] and Zhu et al [25].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Patients with the 609TT and the 609CC genotypes were compared and a strong correlation was observed (OR = 2.04, 95% CI = 1.37-3.05). These authors concluded that the 609C > T polymorphism of the NQO1 gene increases the risk for developing stomach cancer, especially in the Asian population [23]. Similar results were obtained by Liu et al [24] and Zhu et al [25].…”
Section: Discussionsupporting
confidence: 70%
“…In another study of the Asian population, a relationship between the 609C > T oxidoreductase (NQO1) polymorphism and gastric cancer was found and a significantly increased risk (46%) of gastric cancer (95% CI = 1.20-1.79; p < 0.001) was demonstrated in people with the T allele [23]. Patients with the 609TT and the 609CC genotypes were compared and a strong correlation was observed (OR = 2.04, 95% CI = 1.37-3.05).…”
Section: Discussionmentioning
confidence: 98%
“…In fact, a number of other studies also showed that NQO1 rs1800566 polymorphism plays a different role in different cancer site and ethnicity. For example, Ding et al found that NQO1 rs1800566 polymorphism was associated with increased risk of colorectal cancer in Caucasians but not in Asians (Ding et al, 2012), while Zhang et al reported that NQO1 rs1800566 polymorphism is only associated with increased gastric cancer risk in Asians but not in Caucasians (Zhang et al, 2012). On the other hand, there were only four studies involving Asians that were included in our meta-analysis; the relative small sample size may have affected the results.…”
Section: Discussionmentioning
confidence: 84%
“…It has been reported that the NQO1 C609T polymorphism is associated with the risk of many types of malignancies, such as cancers of the stomach [26], breast [27] and esophagus [28]. However, a meta-analysis by Guo et al .…”
Section: Discussionmentioning
confidence: 99%